Debt Counselling for Depression in Primary Care: an adaptive randomised controlled pilot trial (DeCoDer study) - Pippa Anderson (Health Technology Assessment, 2017)
Background: Depression and debt are common in the UK. The DeCoDer trial aimed to assess the clinical and cost effectiveness of the addition of Primary Care debt counselling advice service to usual care, for patients with depression and debt. However, the study was terminated early during the internal pilot trial phase because of recruitment delays. This report describes the rationale, methods and findings of the pilot study, and implications for future research. Objectives: The overarching aim of the internal pilot was to identify and resolve problems, thereby assessing the feasibility of the main trial. Specific objectives were to: confirm methods for practice recruitment, ability to recruit patients via the proposed approaches, determine acceptability of the study interventions and outcome measures; assess contamination, confirm the randomisation method for main trial, the level of participant attrition; and check robustness of data collection systems. Design: Adaptive parallel two group multi-centre randomised controlled pilot trial with nested mixed methods process and economic evaluation. Both individual and cluster (General Practice) level allocation were used in the pilot phase to assign participants to intervention or control groups. Setting: General practices in England and Wales.Participants: Individuals age ≥18 years, scoring ≥14 on the Beck Depression Inventory and self-identifying as having debt worries were included. Main exclusion criteria were: actively suicidal or psychotic and/or severely depressed and unresponsive to treatment, severe addiction to alcohol/illicit drugs, unable/unwilling to give written informed consent, currently participating in other research including follow-up phases, received Citizen’s Advice Bureau (CAB) debt advice in past year, and not wanting debt advice via GP practice. Interventions: Intervention: debt advice provided by CAB and shared biopsychosocial assessment in addition to treatment as usual (TAU) and two debt advice leaflets; Control: advice leaflets provided by GP and TAU only. Outcomes of pilot trial: Proportion of eligible patients who consented; number of participants recruited compared to target; assessment of contamination; assessment of patient satisfaction with intervention and outcome measures.Participant outcomes: Primary: Beck Depression Inventory II; Secondary: Psychological wellbeing, health and social care utilisation, service satisfaction, substance misuse, record of priority/non-priority debts, life events and difficulties and explanatory measures. Outcomes were assessed at baseline (pre-randomisation) and 4-months post randomisation. Other data sources: Qualitative interviews were conducted with participants, clinicians and CAB advisors.Results: Of the 238 expressions of interest screened, 61 participants (26%) were recruited and randomised (32 intervention and 29 control). All participants provided baseline outcomes and 52 provided primary outcome at four months follow up (14.7% drop out). 17 participants allocated to intervention saw CAB. Descriptive statistics are reported for participants with complete outcomes at baseline and 4-months’ follow up. Our qualitative findings suggest that the relationship between debt and depression is complex and the impact of each on the other is compounded by other psychological, social and contextual influences. Conclusions, Study Limitations and Future work: Due to low recruitment this trial was terminated at the internal pilot phase, and too small for inferential statistical analysis. We provide implications for conducting future research in this area.